Tax Policy in the European Union: A Review of Issues and Options - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2002)
As economic integration within the European Union (EU) progresses, the interactions between the tax systems of the Member States are of growing importance. Member State tax policies can have spillover effects on other Member States and differing abilities to provide net fiscal benefits to residents may impair the efficient allocation of productive factors across the EU. These considerations have important implications for the design and coordination of tax systems in the EU. Following a survey of tax developments and a review of the criteria that should govern the tax relationships between the Member States, this paper analyzes the issues and options that Member States face when levying and coordinating their taxes on consumption, labor and capital.
Keywords: 330